Efficacy of vamorolone in treatment of Duchene muscle dystrophy. A meta-analysis - Elhalag, Rowan H.; Motawea, Karam R.; Talat, Nesreen Elsayed; Rouzan, Samah S.; Shah, Jaffer (Frontiers in Neurology, 2023)
Recent studies evaluated the role of vamorolone in treating Duchenne muscular dystrophy (DMD), so we aimed in our Meta-analysis to assess the efficacy of vamorolone in comparison with placebo and corticosteroids for treating DMD patients. Methods: We searched PubMed, Web of Science, Scopus, and Cochrane library databases. We included any randomized control trials and controlled observational studies that investigated the role of vamorolone in treating DMD patients. We used RevMan software, version 5.4. to perform our meta-analysis. Results: After a search of the literature, 4 studies were included in the meta-analysis; the total number of patients included in the study is 277 patients, 125 patients in the vamorolone group, 106 in the glucocorticoids group, and 46 in placebo (steroid naïve) group. The pooled analysis showed a statistically significant association between the vamorolone group and increased TTSTAND velocity, TTRW velocity and TTCLIMB velocity compared with the placebo group (MD = 0.04, 95% CI = 0.02 to 0.07, p-value = 0.002), (MD = 0.24, 95% CI = 0.11 to 0.37, p-value = 0.0003) and (MD = 0.06, 95% CI = 0.05 to 0.06, p-value <0.00001), respectively. Also, the analysis showed a statistically significant association between vamorolone and increased TTRW velocity and increased Height percentile for age compared with the glucocorticoid group (MD = -0.14, 95% CI = -0.26 to -0.01, p-value = 0.03) and (MD = 17.82, 95% CI = 3.89 to 31.75, p-value =0.01), respectively. Conclusion: Our study revealed a significant association between vamorolone and increased TTSTAND velocity, TTRW velocity, and TTCLIMB velocity compared with the placebo (steroid naïve), also showed a statistically significant association between increased TTRW velocity and increased Height percentile for age compared with the glucocorticoid that enhances the privilege of vamorolone over glucocorticoid in treating DMD patients. More multicenter randomized studies are needed to support our results.